A conceptual assessment framework for sustainability in the foundation industries - Litos, Lampros; Paddea, Sanjooram; Salonitis, Konstantinos; Jolly, Mark R. (Elsevier, 2024)
Foundation industries in the UK are in constant pursuit of better technological solutions to enhance materials conversion efficiency and supply chain economies of scale. However, sustainable materials and strategies to conserve resources and better utilize waste streams tend to be ever more challenging to achieve when technological advances fall short in being widely adoptable by companies. Knowledge and technology transfer across multiple companies within the same sector (for example, construction materials production) or across seemingly common core processes (such as size reduction or furnaces) must be achieved for sustainability efforts to achieve economies of scale. Part of the reason why this is a difficult endeavor is the lack of visibility of the steps and drivers involved in a circular economy context with a view to achieve scale. Materials and technologies that could help foundation industries become more sustainable are being examined through the introduction of a novel framework that could help companies and policy makers understand where the opportunities exist. In this paper, the authors describe the design and development of the framework and offer examples drawn from an ongoing research and innovation project in foundation industries.
Keywords: 4014 Manufacturing engineering; foundation industries; sustainability assessment; scalability; technology transfer